Pengembangan Soal Kognitif Berbasis Hots dalam Mata Pelajaran Sejarah pada Pokok Bahasan Perkembangan Kerajaan Islam di Indonesia pada Masa Islam Untuk Siswa Kelas X - Nike Aryanti; Nova Kurnia sari; Rika Cloudya Siregar; Ratu ilma Indra Putri; Sani Safitri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
In education, assessment means the process of collecting and processing information for the purpose of student learning outcomes. To carry out this assessment, the teacher needs an instrument assessment in the form of questions that develop HOTS. In this era, students must have high-order thinking skills (HOTS), one of which is critical thinking. The importance of higher-order thinking skills can be seen from the government's efforts to integrate learning that is strengthened in character education, literacy, HOTS-based learning today. Therefore, this study aims to develop valid HOTS-based questions. With question-based that can be used to measure students' critical thinking. the research model used in this study is an example of the development of Educational Research according to Tessmer. The data analysis technique used is quantitative analysis which aims to determine the validity of the questions. The validity of this development item was obtained based on the verification results of history education teachers. The results of this development were in the form of questions consisting of 10 HOTS-based questions to measure students' critical intelligence, with a discussion of the development of Islam in Indonesia being tested on class X students at SMA N 1 Tanggga Batu.